2010
DOI: 10.1303/aez.2010.521
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the immigration source of rice planthoppers, Nilaparvata lugens (Stål) and Sogatella furcifera (Horváth) (Homoptera: Delphacidae), in Taiwan

Abstract: Since overwintering populations of brown planthopper (Nilaparvata lugens) and white-backed planthopper (Sogatella furcifera) in Taiwan are very low based on field observations, immigrant planthoppers have become the most important source of serious damage to rice crops (Oryza sativa). Backward trajectory analysis was conducted using trap catch data from 1990 to 2005 to estimate the source of immigrant planthoppers, taking into account the emigration periods and weather conditions, and showed that southern Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The dashed arrows on the map of southern Vietnam and Thailand indicate possible migration in March from winter-spring crops, with unknown migration distances. By early May, rice planthoppers reach northern Guangxi, Guangdong, southern Jiangxi, Fujian, and Taiwan from northern Vietnam, Hainan, and already invaded areas in southern Guangxi and Guangdong ( Figure 2A ; Huang et al, 2010 ; Qi et al, 2010a ; Shen et al, 2011a ; Zhao et al, 2011b ). The areas of invasion gradually spread northward by early June as the monsoons penetrate northward ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dashed arrows on the map of southern Vietnam and Thailand indicate possible migration in March from winter-spring crops, with unknown migration distances. By early May, rice planthoppers reach northern Guangxi, Guangdong, southern Jiangxi, Fujian, and Taiwan from northern Vietnam, Hainan, and already invaded areas in southern Guangxi and Guangdong ( Figure 2A ; Huang et al, 2010 ; Qi et al, 2010a ; Shen et al, 2011a ; Zhao et al, 2011b ). The areas of invasion gradually spread northward by early June as the monsoons penetrate northward ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, source areas for S. furcifera immigrants in southern Fujian in April to May from 2007 to 2010 were estimated to be Guangdong and Hainan ( Shen et al, 2011a ). Possible immigration sources in April to May in western Taiwan were also estimated to be Guangdong, Hainan, and the Philippines ( Huang et al, 2010 ).…”
Section: Sogatella Furcifera and Nilaparvata Lugenmentioning
confidence: 99%
“…Until the emergence of SRBSDV, WBPH was studied as a pest of rice but was not considered an important vector of plant viruses. Recent studies of the epidemiology of the vector showed its capability for long‐distance spread (Otuka et al ., ; Huang et al ., ) that have important implications for spread of the virus. In particular, the drastic increase in insecticide resistance among WBPH populations (Tang et al ., ; Matsumura et al ., ) has undoubtedly contributed to greater spread of the insects and also of SRBSDV.…”
Section: Epidemiologymentioning
confidence: 99%
“…The migration sources and dispersal patterns within the region have been examined by several researchers in recent years. For example, a number of studies have begun to explore the migration sources of the WBPH based on the trajectory analyses methods 1 6 . Due to their small body size, short lifespan, and long distance dispersal capability, it has been difficult to use fluorescent marker dyes, radar monitoring or other conventional approaches to study the migration of these insects 7 .…”
Section: Introductionmentioning
confidence: 99%